(untitled) (Al Dzahab, 2022)
Purpose: This study aims to find out the implementation of the program Corporate social responsibility by the company which is exemplified by PT Kimia Farma and how to implement the program from an Islamic point of view. Design/methodology/approach: This study uses a qualitative method with the type of literature review or library research. The sample of this research is Corporate social responsibility conducted by PT Kimia Farma .Tbk which is quoted from the annual report of PT Kimia Farma .Tbk which is then reviewed and viewed from an Islamic perspective. Findings: CSR activities can ultimately improve the standard of living and provide benefits for the company itself, the surrounding community, and the general public. Various CSR consists of economic responsibility, legal responsibility, ethical responsibility, and charitable responsibility. As exemplified in the case study by the implementation of Corporate Social Responsibility by PT Kimia Farma. Research implications: The results of this study are expected to contribute to the literature on companies by providing an illustration that CSR activities and views from an Islamic perspective are equally important business strategies in creating a superior sustainable future for companies that will have an impact on the social environment not only physically. but also the trust of local communities and stakeholders based on voluntary principles.